2016
DOI: 10.1007/s00220-016-2578-y
|View full text |Cite
|
Sign up to set email alerts
|

Superdiffusion in the Periodic Lorentz Gas

Abstract: We prove a superdiffusive central limit theorem for the displacement of a test particle in the periodic Lorentz gas in the limit of large times t and low scatterer densities (Boltzmann-Grad limit). The normalization factor is √ t log t, where t is measured in units of the mean collision time. This result holds in any dimension and for a general class of finite-range scattering potentials. We also establish the corresponding invariance principle, i.e., the weak convergence of the particle dynamics to Brownian m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
61
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(63 citation statements)
references
References 29 publications
2
61
0
Order By: Relevance
“…We thus expect a classical diffusion equation with a non-classical coefficient in the asymptotic limit. For this simplified equation, this reproduces the result of Marklof & Tóth [13] who proved a superdiffusive central limit theorem directly for the particle billards underlying the periodic Lorentz gas equation. They showed that the periodic Lorentz gas is superdiffusive, but only logarithmically.…”
Section: Concluding Remarks and Future Worksupporting
confidence: 83%
“…We thus expect a classical diffusion equation with a non-classical coefficient in the asymptotic limit. For this simplified equation, this reproduces the result of Marklof & Tóth [13] who proved a superdiffusive central limit theorem directly for the particle billards underlying the periodic Lorentz gas equation. They showed that the periodic Lorentz gas is superdiffusive, but only logarithmically.…”
Section: Concluding Remarks and Future Worksupporting
confidence: 83%
“…Theorem 3.2: the particle density is approximately linear (point particles are enlarged for better visibility).case. Case (i) has been analyzed in [6] for periodic Lorentz gas and in [3,17,28] for random Lorentz gas in the Boltzmann-Grad limit (see also [2,23] for recent results on deterministic motion in the Boltzmann-Grad limit). Case (ii) has been studied in [15] for periodic Lorentz gas and in [20] for random Lorentz gas in the Boltzmann-Grad limit.…”
mentioning
confidence: 99%
“…(19) despite the differing manner in which the limit is taken [18]. Marklof and Tóth have recently proved a central limit theorem, also in arbitary dimension [113]. Their approach, which uses dynamics in the space of lattices, has also led to interesting results in other fields, such as the distribution of Frobenius numbers [114].…”
Section: The Boltzmann-grad Limitmentioning
confidence: 99%